Experience with an Enteral-Based Nutritional Support Regimen in Critically-Ill Trauma Patients - Chung, Christina K (2013)
BACKGROUND: Assuring adequate enteral nutritional support in critically ill patients is challenging. By describing our experience we sought to characterize the challenges, benefits and complications of an approach that stresses enteral nutrition (EN). STUDY DESIGN: We examined nutritional support received by victims of blunt trauma from eight trauma centers. We grouped subjects according to the average daily enteral caloric intake over the first 7. Group 1 received the fewest (0 kcal/kg/day) and group 5 the greatest (16 – 30 kcal/kg/day) number of calories in the first week. We focused our analyses on the patients remaining in the ICU for ≥ 8 days and compared clinical outcomes among the groups. RESULTS: 1100 subjects were in the ICU for ≥8 days. Patients receiving the greatest number of enteral calories during the first week (group 5) had the highest incidence of VAP (49%) and the lowest incidence of bacteremia (14%). The use of parenteral nutrition was associated with bacteremia (aOR = 2.5, 95% CI = 1.8 – 3.5), VAP (aOR = 2.4, 95% CI = 1.7 – 3.3) and death (aOR = 1.9, 95% CI = 1.1 – 3.1) CONCLUSIONS: Enteral caloric intake during the first week was related to the pattern and severity of injury and associated with important infectious outcomes. Our observations support moderating enteral intake during the first week after injury and avoiding parenteral nutrition.